Balanced and energy‐efficient multi‐hop techniques for routing in wireless sensor networks. Issue 1 (1st January 2018) - Fawzy, Abd Elwahab; Shokair, Mona; Saad, Waleed
Abstract : In Wireless Sensor Networks, the power resources of the nodes are significantly restricted. Hence, a special treatment for their available energy is deeply required. In long distance transmission, Multi‐Hop (MH) techniques are preferred. Although MH minimizes the amount of energy cost consumed by each node along the path but finding the optimal routing path between nodes is still very interesting issues. This paper proposes a Balanced and Energy Efficient MH (BEEMH) algorithm that is developed based on Dijkstra algorithm. It gives great interest to the residual energy of nodes; hence higher energy nodes are exclusively elected to work as relays. Moreover, the total energy consumption at both TX and RX has been merged to model the weight of links between nodes. Finally, Dijkstra algorithm is employed to efficiently search for the minimum cost path. Furthermore, two proposed MH protocols are introduced. Both are mainly based on the BEEMH algorithm. MATLAB simulator has been used to evaluate BEEMH in comparison with other conventional algorithms such as; minimum transmission energy (MTE), energy saving oriented least‐hop routing algorithm (ESLHA), and energy saving‐oriented routing algorithm based on Dijkstra (ESRAD) under various scenarios of network models. Then the performance of our proposed protocols is compared with the related MH protocols.